Role of a sugar-lipid intermediate in colanic acid synthesis by Escherichia coli. - Johnson, J G (1977)
Membrane fractions from a lon strain of Escherichia coli but not a wild-type strain catalyze the incorporation of fucose from guanosine 5'-diphosphate-fucose into a lipid and into polymeric material. Both incorporation reactions specifically require only uridine 5'-diphosphate (UDP)-glucose. The sugar lipid was shown to be an intermediate in the synthesis of the polymer which was related to colanic acid. The sugar lipid had the structure (fucose3, glucose2)-glucose P-P-lipid. Its behavior on column and thin-layer chromatography, the rates of its hydrolysis in acid and base, and the response of its synthesis to inhibitors are all identical to the other sugar-lipid intermediates which have been shown to contain sugars attached to the C55-polyisoprenol, undecaprenol, by a pyrophosphate linkage. The membrane fractions from both the lon strain and the wild-type strain also catalyzed the incorporation of either glucose from UDP-glucose or galactose from UDP-galactose into a lipid fraction which was shown to contain the free sugar attached by a monophosphate linkage to an undecaprenol-like lipid. This lipid was isolated and its nuclear magnetic resonance spectra was identical to undecaprenol. The membrane fractions from both strains also incorporated glucose from UDP-glucose into glycogen and into a polymer that behaved like Escherichia coli lipopolysaccharide. Conditions were found where the incorporation of glucose could be directed specifically into each compound by adding the appropriate inhibitors.